2023
DOI: 10.7554/elife.82112
|View full text |Cite
|
Sign up to set email alerts
|

Csf1 from marrow adipogenic precursors is required for osteoclast formation and hematopoiesis in bone

Abstract: Colony stimulating factor 1 (Csf1) is an essential growth factor for osteoclast progenitors and an important regulator for bone resorption. It remains elusive which mesenchymal cells synthesize Csf1 to stimulate osteoclastogenesis. We recently identified a novel mesenchymal cell population, marrow adipogenic lineage precursors (MALPs), in bone. Compared to other mesenchymal subpopulations, MALPs expressed Csf1 at a much higher level and this expression was further increased during aging. To investigate its rol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
2
11
1
Order By: Relevance
“…Within the non-hematopoietic cells, we identified three major lineages – vascular smooth muscle ( ACTA2 , RGS5, TAGLN ), endothelial cells ( CDH5 , PECAM1, VWF ), and mesenchymal cells ( CXCL12, PDGFRA) including osteolineage cells and mesenchymal stromal cells (MSCs) (Figure 1B-D, Supplemental Table S2, Supplemental Figure S1E). Contrary to previous results from human bone marrow aspirate samples 19 which found that MSCs were relatively homogenous and expressed an adipocytic transcriptional profile 23 , we observed that mesenchymal stromal cells from digested bone marrow were highly heterogenous with numerous clusters identified (Figure 1B, Supplemental Figure 1F).…”
Section: Resultscontrasting
confidence: 99%
“…Within the non-hematopoietic cells, we identified three major lineages – vascular smooth muscle ( ACTA2 , RGS5, TAGLN ), endothelial cells ( CDH5 , PECAM1, VWF ), and mesenchymal cells ( CXCL12, PDGFRA) including osteolineage cells and mesenchymal stromal cells (MSCs) (Figure 1B-D, Supplemental Table S2, Supplemental Figure S1E). Contrary to previous results from human bone marrow aspirate samples 19 which found that MSCs were relatively homogenous and expressed an adipocytic transcriptional profile 23 , we observed that mesenchymal stromal cells from digested bone marrow were highly heterogenous with numerous clusters identified (Figure 1B, Supplemental Figure 1F).…”
Section: Resultscontrasting
confidence: 99%
“…RANKL production by MALPs was shown to be essential for bone homeostasis, which was confirmed by independent research groups 40,41 . Moreover, it was previously assumed that osteoblasts and mature bone marrow adipocytes were the main producers of M-CSF in the bone, however recent evidence shows that MALPs are likely the main source of M-CSF 40,42 . Finally, to the best of our knowledge, we are the first to document the existence of MALPs in human and to show that they express the bAR.…”
Section: Discussionmentioning
confidence: 99%
“…The BM adipocyte differentiation axis is gaining attention as a fundamental component of bone and blood physiology, with several recent studies focusing on the BM stroma population as a key player in the maintenance of the balance between bone and BM space 8,55 . Ablation of the BM adipocyte precursor population leads to massive accumulation of bone in the medullary cavity 4,7,14,52,54 which in turn reduces the volume available for hematopoietic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The bone, long considered a merely structural organ, is now seen as a highly dynamic tissue in which various processes, including hematopoiesis, bone remodeling, immunity and metabolism are tightly regulated 1,2 . These processes rely on specialized microenvironments, termed niches, that play a critical role in cell fate regulation 3 , with the bone marrow adipose tissue (BMAT) being an emerging niche component [4][5][6][7][8] . The bone marrow (BM) niche regulates hematopoietic stem and progenitor cell (HSPC) quiescence, self-renewal and commitment towards differentiated cells thanks to a combination of soluble factors and cell-cell interactions 1,3,9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation